Hidrodinamski pojavi pri izhlapevanju kapljic - Uršič, Urša (Matrika, 2019)
Coffee stain effect occurs in droplets with pinned contact line. Without pinning, the evaporation of fluid would move the contact line towards the centre. In the case with a pinned contact line the fluid near edge must be compensated with an outward radial flow. This is a laminar flow that carries potential colloid particles towards the contact line, resulting in an nonuniform stain after the fluid is evaporated. Marangoni flow is guided by the surface tension gradient, which occurs due to temperature gradient or concentration gradient in multicomponent droplets. The flow is radial and vortical.
Keywords: coffee stain effect; droplets; efekt kavnega obroča; evaporation; hidrodinamika; hydrodynamics; izhlapevanje kapljevine; kapljice